Perbandingan Ketamin Dosis 0.5 mg/KgBB/IV dan 1 mg/KgBB/IV Sebagai Preemptif Analgesia pada Paska Operasi Ginekologi dengan Anestesi Umum - Andri Yunafri; A Sani P Nasution (Universitas Muhammadiyah Sumatera Utara, 2018)
Abstract: Excitatory amino acids participate in the activation of nociceptive dorsal horn neurons as agonists of the N-methyl-D-aspartate (NMDA) receptor. A series of experimental data provides evidence that NMDA receptors play a significant role in neuronal plasticity and processes leading to central sensitization to pain. The concept of preemptive analgesia on the assumption that the administration of an analgesic drug before the occurrence of nociceptive input can prevent sensitization and thus improve postoperative analgesia. The aim of our study was to test the hypothesis that preemptive ketamine administration would further reduce postoperative pain in gynecology surgery. After institutional review board approved the study protocol, all patients gave informed, written consent. 60 patients were randomized to a preemptive Ketamine 0.5 mg/kg/iv (Group A) or Ketamine 1 mg/kg/iv (Group B). Preoperatively visual analog scale (VAS) for pain assessment. Patient received premedication with midazolam 0.1 mg/kg iv, sulfas atropin 0.01 mg/kg at the operating room. Anesthesia was induced with propofol 2 mg/kg/iv, fentanyl 2 μg/kg/iv, and rocuronium 1 mg/kg/iv was administered to facilitate tracheal intubation. Maintenance of anesthesia consisted of O2:N2O = 50%:50% and isoflurane 1%. In both groups, ketamine bolus IV was administered after induction of general anesthesia and 10 minute before incision. HR and BP was recorded during operation. Post operative pain assessed with VAS at 0.5, 1, 2, 8, 16, and 24 hour. Time first analgesic (TFA) was recorded, and if VAS pain scores > 3 cm (0= no pain, 10 = worst pain imaginable). Total fentanyl consumption were recorded for the post surgery. The first analgesic required time was significantly shorter in groups A as compared with group B (p=0.0001). Group B had significantly decreased postoperative pain scores (VAS) at 0.5, 1, and 2 hours (p<0.05). There were no statistically significant differences VAS score between the two grups at 8, 16, and 24 hours post surgery (p>0.05). Conclusion, ketamine 1 mg/kg intravena provide better preemptive analgesia in the first 2 hours post surgery, but both groups perform the same preemptive analgesia within 24 hours of post gynecology operation.Key words: analgesia; ketamine; preemptive; gynecology; surgery pain